2017
DOI: 10.1155/2017/2302896
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Alleviates Endotoxin‐Induced Myocardial Toxicity by Modulating Inflammation, Oxidative Stress, and Autophagy

Abstract: Apigenin, a component in daily diets, demonstrates antioxidant and anti-inflammatory properties. Here, we intended to explore the mechanism of apigenin-mediated endotoxin-induced myocardial injury and its role in the interplay among inflammation, oxidative stress, and autophagy. In our lipopolysaccharide- (LPS-) induced myocardial injury model, apigenin ameliorated cardiac injury (lactate dehydrogenase (LDH) and creatine kinase (CK)), cell death (TUNEL staining, DNA fragmentation, and PARP activity), and tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 67 publications
(72 reference statements)
2
47
0
Order By: Relevance
“…Earlier research reported the effect of API on autophagy. Fang et al found that API promoted autophagy and alleviated myocardial oxidative and inflammatory injury, and endotoxininduced myocardial toxicity (Li et al, 2017). Additionally, API plays an anti-tumor role by promoting autophagy in various tumors such as skin cancer (Bridgeman et al, 2016), colon cancer (Lee et al, 2014;Chen et al, 2019), thyroid carcinoma (Zhang et al, 2015), and hepatocellular carcinoma (Gao et al, 2018;Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research reported the effect of API on autophagy. Fang et al found that API promoted autophagy and alleviated myocardial oxidative and inflammatory injury, and endotoxininduced myocardial toxicity (Li et al, 2017). Additionally, API plays an anti-tumor role by promoting autophagy in various tumors such as skin cancer (Bridgeman et al, 2016), colon cancer (Lee et al, 2014;Chen et al, 2019), thyroid carcinoma (Zhang et al, 2015), and hepatocellular carcinoma (Gao et al, 2018;Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They established that apigenin can promote ABCC1-mediated glutathione efflux from P. falciparum infected erythrocytes and impede parasite proliferation. In the cardiovascular system, Li et al [44] found that apigenin can protect against endotoxininduced myocardial injury and improve cardiac function by regulating oxidative stress and inflammation in vivo. In myocardial ischemia/reperfusion (I/R) mice, treatment with apigenin decreased infarct size and the release of lactate dehydrogenase (LDH) and creatine kinase (CK).…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin (AP) is a bioactive flavonoid which is obtained from several fruits and vegetables. AP has been reported to exhibit antioxidant, anti-inflammatory, and anticancer activities [16,17]. Our previous study has shown that AP exhibited protective effects on ARPE-19 cells against tert-butyl hydroperoxide-(t-BHP-) induced oxidative injury, which were associated with its antioxidant properties dependent upon the activation of Nrf2 signaling [18].…”
Section: Introductionmentioning
confidence: 99%